2003 5th International Conference on ASIC. Proceedings (IEEE Cat. No.03TH8690)
DOI: 10.1109/issm.2003.1243332
|View full text |Cite
|
Sign up to set email alerts
|

Contamination control of a corona discharge air ionizer

Abstract: A corona discharge air ionizer is one of the most usefill equipment to control electrostatic charges on ULSI in the manufacturing processes. However, a conventional air ionizer generates various kinds of contamination. The dual jet air ionizer that has a jet emitter in a nozzle was proposed to reduce the contamination from an air ionizer. The ozone generation, the particle generation, and the cluster-7ike material growth to the emitter tip were investigated for the dual jet air ionizer as a function of the jet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Particle generation might be reduced by decreasing applied voltage (Romay et al, 1994). A dual jet design also reduced the particle generation from an air ionizer (Takeuchi et al, 2003). In this work, it has been confirmed that the particle generation by ESP could be affected by air velocity, temperature and electric field strength.…”
Section: Resultssupporting
confidence: 56%
“…Particle generation might be reduced by decreasing applied voltage (Romay et al, 1994). A dual jet design also reduced the particle generation from an air ionizer (Takeuchi et al, 2003). In this work, it has been confirmed that the particle generation by ESP could be affected by air velocity, temperature and electric field strength.…”
Section: Resultssupporting
confidence: 56%
“…Electrode pitting can lead to some electrode particles being ejected from the electrode surface, causing a gradual loss of mass [191]. In addition, the emitter electrode can collect contaminates along its surface during a discharge [192,193]. These corrosive effects act to modify the surface of the electrodes and alter the surrounding electric field lines.…”
Section: Ongoing Challenges With the Development Of Ehd Devicesmentioning
confidence: 99%
“…In the manufacturing processes of these electronic devices, particularly the semiconductor and magnetic recording devices, electrostatic charges could lead to the destruction of these devices because of electrostatic discharge (ESD) damage (1) . Electrostatic charges also increase the attraction of unwanted particulate contaminants onto the surface of the devices; this phenomenon is commonly referred to as electrostatic attraction (ESA) (2) (3) . In the manufacturing process, electrostatic charges and ESD/ESA events may also cause machine interruptions and operational errors (3)- (5) .…”
Section: Introductionmentioning
confidence: 99%